The Dynamics of Village Treasury Land Management to Provide Legal Certainty and Benefits - Ropii, Imam; Chrisdanty, Febry; Candra Kusuma, Ariska Cesar Divian (Trunojoyo Madura University, 2024)
The management of village treasury land in Sukolilo Village faces various challenges that deviate from the provisions, especially related to the issue of securing and utilizing village assets. This study aims to examine legal management such as securing and utilizing village treasury land in Sukolilo Village in order to provide legal certainty and benefits for the community. This study uses an empirical or socio-legal method, with a sociological approach to examine the implementation, legal dynamics, and challenges of managing village treasury land in Sukolilo Village, East Java, Indonesia. Regarding security, the land certification process that is designated as part of the village treasury land in Sukolilo Village is still incomplete. Regarding its utilization, buildings utilized by outside parties do not provide economic benefits to the village because they do not have official permits from the village government. The absence of village regulations or directions from the village leadership also creates a legal vacuum. The Sukolilo Village Government needs to immediately register village treasury land and enter into legal agreements stipulated through village regulations. Expansion of the utilization of village treasury land can be done by building tourist villages, utilizing village potential by involving various community groups.